WHAT HAPPENS AFTER THE RIGHT TO COUNSEL ENDS? USING TECHNOLOGY TO ASSIST PETITIONERS IN STATE POSTCONVICTION PETITIONS AND FEDERAL HABEAS REVIEW. - Smilowitz, Margaret (Journal of Criminal Law & Criminology)
The right to counsel ends after an individual loses his direct appeal. There are, however, several opportunities for judicial review available to a prisoner, including statutory post-conviction petitions and federal habeas review. Yet state prisoners often cannot pay for counsel during their collateral review, leaving most prisoners to file pro se. Filing for collateral review is a substantively and procedurally complicated process and pro se petitioners have little guidance. The Supreme Court's jurisprudence on prisoners' access to legal research and knowledge is unclear--prisoners must have meaningful access to court but prisons are not required to provide law libraries or legal assistance. Although other opportunities for legal advice are available--such as jailhouse attorneys, pro bono clinics, and information packets--they generally fail to provide enough assistance for pro se petitioners to meaningfully seek collateral review. Without legal assistance, pro se petitioners file procedurally defaulted claims, which back up state court and federal district court dockets. This Comment proposes that state prison systems provide a computer program for state prisoners who lose their direct appeals. The program would provide the prisoners with detailed assistance to make their way through collateral review. Petitions that are well-pled will better serve the constitutional right to habeas review and will promote judicial economy.